RECONSTRUING URBAN MUSLIM ENTREPRENEUR PROGRAM ON VOLUNTARY ALMSGIVING: Deconstruction, Social Theology and Plurality - Roma Ulinnuha (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
In social realm, the experience of religious communities has created diverse pious space in response to the elevating number of the urban poverty. Religious expression reduces the problem of poverty. The acts gave responses to modernity challenge, as pointed out in Weberian view, that characterized in selfish individualism and egocentrism. Sedekah as a concept of almsgiving sometimes correlated to the charity and philanthropy, but it also serves as complementary vision. This article seeks to employ the deconstruction of almsgiving program among the representative of Muslim urban entrepreneur. It aims at uncover the inspiration of voluntary almsgiving program in urban setting. Applying qualitative method, the article uses empirical secondary data found in both literature and netnography. Applying social theology approach that combined the hybrid theological and sociological ones, the argument exemplifies the alternative reading on sedekah program initiated by Jusuf Hamka, one of urban Muslim entrepreneurs. The article suggests the praxis of voluntary almsgiving program gave a way to inspiration that akin to active and equal traits amid diverse socio-religious practice and social classes. The deconstruction of sedekah program constitutes the pluralist view which is needed in a more democratic and diverse type of society in urban setting.